The role of penile reconstruction in gender affirmation surgery. Issue 6 (24th November 2021) - Lee, Wai Gin; Ralph, David
Abstract : Genital gender affirmation surgery is becoming increasingly sought after, not least because it improves the quality of life of transmasculine individuals. A number of procedures are involved, and they should be tailored to the needs of each individual after appropriate assessment and counselling.